Taxonomic notes on the Acanthopsis disperma-hoffmannseggiana complex (Acanthaceae, tribe Acantheae), with an interim key to members of the genus - Steyn, Hester Maria; van Wyk, Abraham E (Phytotaxa, 2015)
Acanthopsis is a taxonomically poorly understood genus confined to arid parts of southern Africa. This contribution is the first detailed assessment of the diversity within the Acanthopsis disperma-hoffmannseggiana complex, the latter of which comprises the bulk of the specimens of the genus represented in herbaria. Species concepts are resolved and the misapplication of names is noted. In addition to the recognition of A. disperma and A. hoffmannseggiana, five new species of Acanthopsis formerly treated under these two names, are described, namely A. tuba and A. ludoviciana (both confined to the Richtersveld, Northern Cape, South Africa), A. adamanticola (endemic to southern Namibia), A. villosa (endemic to Bushmanland, Northern Cape) and A. dispermoides (endemic to the Western Cape, South Africa). The names A. disperma and A. hoffmannseggiana are lectotypified here. An identification key to the members of the Acanthopsis disperma-hoffmannseggiana complex is provided, as well as an interim key to the major artificial groupings in the genus, the taxonomy of some which still needs to be resolved.